The Effectiveness of Leadership Styles and Strategies to Improve Nurses‘ Electronic Medical Record Quality Based on Kurt Lewin’s Theory - Hidayat, Imat; Purwarini, Justina; Susilo, Wilhelmus Hary (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: This research aims to determine the effectiveness of the leadership style and strategy to improve the quality of nurses' electronic medical records through Kurt Lewin's theoretical Methods:  This research was quasi-experimental. A total of 91 nurses were participate as a respondents. Data collection was used leadership style questionnaire, Kurt Lewin-based leadership strategies and electronic medical record quality form. The intervention was carried out for 2 weeks and was divided into 3 stages, namely the unfreezing stage, moving stage and refreezing stage. The data analysis used was Wilcoxon test. Results: The study found that a leadership style change from authoritarian to democratic was observed in the nursing profession. The intervention led to an improvement in the quality of Electronic Medical Records (EMR) from not achieved to achieved. The intervention also led to a significant improvement in EMR quality, with 73 respondents experiencing a change from not achieved to achieved.   Conclusions: Leadership style changes based on organizational conditions. Leaders must analyze members' characteristics to choose the right style. Kurt Lewin's theory provides leadership strategy training, guiding leaders in making changes step by step. Hospitals should facilitate training to improve nursing room heads' knowledge and quality.